Waste Management Trends Toward Circular Economy (2025)
Waste management has become a global challenge, significantly contributing to widespread pollution due to escalating waste generation. There is an urgent need to transition waste management strategies towards a circular economy. This insightful approach addresses key aspects such as waste minimisation, recycling and reuse, and resource recovery, highlighting the fiscal benefits involved.This book delves into recent discoveries of advanced pollution reduction techniques, innovative waste conversion methods, and unique fabrication processes that are reshaping the field of waste management. Through detailed analysis and case studies, it offers a comprehensive understanding of how these progressive methods are paving the way toward a more sustainable future, emphasising the importance of adopting a circular economy model for effective waste management globally.This book is a crucial resource for researchers, industry professionals, and government sectors, providing valuable insights to enhance decision-making in waste management.